The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/healthcare11081179
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and Threats of the Legally Facilitated Performance-Based Managed Entry Agreements in Slovakia: The Early-Adoption Perspective

Abstract: Slovakia has adopted an amendment to Act No. 363/2011, regulating, among other things, drug reimbursement and is undergoing a significant change in the availability of innovative treatments for patients. High expectations are associated with arrangements related to performance-based managed entry agreements. Opinions and positions towards this change appear to be inconsistent, and for the further application of the law in practice and when setting up the main implementation processes, it is necessary to unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
(23 reference statements)
1
2
0
Order By: Relevance
“…Gerkens et al [ 13 ] highlight that the weaknesses and challenges of PB MEAs include manufacturer concerns about data sharing, regulatory and administrative costs, transferability of results and potential disincentives for providing data. Similar concerns were reported previously in our study in Slovakia [ 12 ]. Rotar [ 15 ] adds that mature HTA systems and robust IT infrastructure may be needed for some PB MEAs.…”
Section: Introductionsupporting
confidence: 93%
See 2 more Smart Citations
“…Gerkens et al [ 13 ] highlight that the weaknesses and challenges of PB MEAs include manufacturer concerns about data sharing, regulatory and administrative costs, transferability of results and potential disincentives for providing data. Similar concerns were reported previously in our study in Slovakia [ 12 ]. Rotar [ 15 ] adds that mature HTA systems and robust IT infrastructure may be needed for some PB MEAs.…”
Section: Introductionsupporting
confidence: 93%
“…As a system, it necessitates highly reliable information processes built on trustworthy data. In the Czech Republic, as well as in Slovakia [ 12 ], and likely in other regions, significant gaps still exist in this regard.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The OECD report revealed that in most EU countries, including Poland, Bulgaria, and Romania, financial-and performance-based managed entry agreements are available [22]. Slovakia recently adopted a new regulation in terms of pricing and reimbursement, and the advantages of the new introduced mechanisms are still being investigated [23].…”
Section: Discussionmentioning
confidence: 99%